On computing the geoelastic response to a disk load. Issue 3 (30th March 2016) - Bevis, M.; Melini, D.; Spada, G.
Abstract: We review the theory of the Earth's elastic and gravitational response to a surface disk load. The solutions for displacement of the surface and the geoid are developed using expansions of Legendre polynomials, their derivatives and the load Love numbers. We provide a matlab  function called diskload that computes the solutions for both uncompensated and compensated disk loads. In order to numerically implement the Legendre expansions, it is necessary to choose a harmonic degree, n max, at which to truncate the series used to construct the solutions. We present a rule of thumb (ROT) for choosing an appropriate value of n max, describe the consequences of truncating the expansions prematurely and provide a means to judiciously violate the ROT when that becomes a practical necessity.